The Concept of Character Education Perspective of Ki Hajar Dewantara and KH Imam Zarkasyi and Their Relevance With The 2013 Curriculum - Shofwan Almuzani; Gatot Handoko; Maksudin Maksudin (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
morals and akhlaq are formed through caracter education, in other it's able to form productive, creative, and noble personality. The character of a nation is faced with complex problems. Among them are some high school sudents caught carrying machetes just before gang's brawl, and the next case is the beating by the youth of the klitih group to a person named Agung Styobudi in the Sleman city. Based on the facts, the researchers tried to express and compare the concept of character education between the perspectives of Ki Hajar Dewantara and KH Imam Zarkasyi with a socio-historical approach and analyze the relevance of thinking to the 2013 curriculum, which is expected to be a solutions. The research resulted in several concepts: the concept of character education according to Ki Hajar Dewantara, is a science that studies the good and bad of human attitudes, so that it can be applied in everyday life, the orientation is a liberating science. Meanwhile, character education according to KH Imam Zarkasyi: is a philosophy of life that includes sincerity, simplicity, independence, ukhuwah Islamiyah, and freedom, the orientation is religious values, which contain elements of belief (i'tikad), elements of character, and elements of feelings. The basis of the concept of character education Ki Hajar Dewantara and KH Imam Zarkasyi both produced the concept of character education which was implemented in the 2013 curriculum according to the cognitive, affective, and psychomotor domains, which followed the achievement of graduate competency standards. The analysis of the relevance of character education from the thoughts of the two figures according to the 2013 curriculum resulted: The concept of character education KH Imam Zarkasyi is more relevant to the 2013 curriculum, due to the many conformities of the concept of character education which is based on the teachings of noble character and Islamic teachings, the main learning method is habituation, while the content and teaching resources include religious and character subjects and are based on the achievement of graduate competencies.